Розробка компонентів crm системи для дрібної мобільної торгівлі - Кузьмін, А. А. (ХНУРЕ, 2023)
This work is devoted to CRM system components for small mobile commerce. The problems of lack of access to effective tools for managing interaction with customers in DMT enterprises are investigated. To solve this problem, research was conducted and components of the CRM system were developed, which allow automating and optimizing business processes related to the management of interaction with customers. The work describes the research methods that were used to develop the components of the CRM system, and the results of the research are presented. The developed components include modules for customer database management, sales, marketing and reporting, and have been tested in practice in real conditions